Inhibition of premature transient boiling crisis induced by heat-load step pulses in a helium natural circulation loop by dynamic initial condition. (August 2018) - Furci, H.; Baudouy, B.; Four, A.
Highlights: Transients induced by power step-pulses on boiling helium natural circulation loop. Transient boiling crisis (BC) onset is characterized as a function of initial condition. BC regime maps are determined on the initial-final heat flux plane. A general quality-transport-based criterion is found for the bulk-dominated regime. Abstract: Boiling helium natural circulation loops constitute a cooling option for large superconducting magnets. Their steady state thermalhydraulic behavior has already been studied quite thoroughly. However, the transient response of these systems has started being studied only recently. Although transient boiling experiments with other fluids or heating configurations exist, their findings are difficult to extrapolate to the case of natural circulation loops. In this work, we present the continuation of an experimental study on helium natural circulation loops. In this case, the system is excited by a stepwise power increase from a dynamic initial condition (a stable initial heat flux is applied). Boiling crisis onset during the transient was identified from the measurement of wall temperature on the heated section. The increase of the initial heat flux and the consequent initial flow increase have been found to have a partial or complete inhibiting effect on transient boiling crisis onset in the premature boiling crisis regime with respect to the static initial condition case. Behavior charts could be drawn on the initial-final heat flux plane. A general empirical criterion based on the evolution of vapor fraction along the section is provided for the prediction of boiling crisis onset by this mechanism.